Alzheimer's disease. Correlation of cortical choline acetyltransferase activity with the severity of dementia and histological abnormalities. - Wilcock, G; Esiri, M; Bowen, D; Smith, C (1982)
We have examined the choline acetyltransferase [CAT] activity in autopsy samples of frontal and temporal lobe cortex from 47 patients (31 with Alzheimer's disease, 4 with dementia due to cerebrovascular disease and 12 undemented controls) and compared it with the severity of dementia during life and with the numbers of argyrophilic plaques and neurofibrillary tangles in the corresponding areas of cortex in the contralateral cerebral hemisphere. CAT activity was significantly reduced, most severely in the temporal lobe, in patients with Alzheimer's disease but not in patients with a cerebrovascular cause for their dementia, and CAT activity showed no significant reduction with age in the undemented control patients. In the patients with Alzheimer's disease the reduction in CAT activity was significantly correlated with the severity of dementia and with the numbers of neurofibrillary tangles, but not argyrophilic plaques, present in the corresponding contralateral cortex.